PERAN BPD DALAM MENDUKUNG PEMERINTAH DESA UNTUK MEWUJUDKAN GOOD GOVERNANCE DI DESA SUMBERKEPUH KEC.TANJUNGANOM KABUPATEN NGANJUK - Yenik Pujowati (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2017)
After the transition of the regime from the new order to the reform of the State gave rise to Law no. 28 of 1999. In the regulation, it becomes the seven principles and serves as the guidance for all State apparatus to carry out the task. The seven principles cover the principles of legal certainty, the principles of orderliness, the principles of public interest, the principles of transparency, the principle of proportionality, the principle of professionalism and the principle of accountability. Regional autonomy is also divided into Provincial, Regency / Municipal Governance and Village Government. Village Government is said to be an autonomous government because in Law no. 6 Year 2014, the village is a legal community unit which has the authority to administer and regulate the interests of the local community based on customs and origins recognized by the State. Thus the village government does not depend entirely on the government above it in the affairs of the implementation of Village Government. Villages also have the authority to organize democratic parties and the election of village heads and BPD institutions is a manifestation of the democracy.